2011
DOI: 10.5114/aoms.2011.24126
|View full text |Cite
|
Sign up to set email alerts
|

Detection of 1311 polymorphism in the glucose-6-phosphate dehydrogenase gene by microarray technique

Abstract: IntroductionNucleotide 1311 polymorphism at exon 11 of the glucose-6-phosphate dehydrogenase (G6PD) gene is fairly common in various populations worldwide, especially among Mediterranean populations. In this study, 1311 polymorphism in G6PD-deficient cases was identified by microarray technique.Material and methodsFour hundred and fifty clinically healthy subjects were screened and 32 cases were found to have G6PD deficiency (7.11%). Our analysis of genomic DNA samples from 32 G6PD-deficient individuals reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Nucleotide position 1311(C>T) was regarded as a silent polymorphism, and could not result in the substitution at the amino acid level. The c.1311C>T polymorphism was widely detected among the G6PD deficient and normal population with various frequencies 15 , 22 , 23 . The prevalence of c.1311C>T in this study was similar to that in most of the previous studies 15 , 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Nucleotide position 1311(C>T) was regarded as a silent polymorphism, and could not result in the substitution at the amino acid level. The c.1311C>T polymorphism was widely detected among the G6PD deficient and normal population with various frequencies 15 , 22 , 23 . The prevalence of c.1311C>T in this study was similar to that in most of the previous studies 15 , 23 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, Özlü found the frequency of G6PD deficiency to be 3% in male infants (15). In another study conducted in the Çukurova region by Menziletoglu Yildiz et al, they found the frequency of G6PD deficiency to be 7.11% in 450 healthy individuals (16). In a study conducted with 1421 healthy individuals living in Balıkesir and Çanakkale, the frequency of G6PD deficiency was found to be 7.24% in female, 6.2% in male, and 6.9% in all cases (17).…”
Section: Discussionmentioning
confidence: 94%